Pengaruh Social Media Marketing Tiktok dan Content Creator Terhadap Keputusan Pembelian Produk Skintific di Kota Mataram - Ni Nyoman Gita Santi Ananda; Didy Ika Supryadi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to investigate the influence of TikTok social media marketing and content creators on purchasing decisions for Skintific products in Mataram City. This associative research uses a quantitative approach with a sample size of 100 respondents. Data analysis was performed using SPSS software. The results show that TikTok social media marketing and content creators have a positive and significant impact on purchasing decisions for Skintific products in Mataram City. Based on these findings, it can be concluded that TikTok social media marketing and content creators play a crucial role in increasing purchasing decisions for Skintific products in Mataram City. The researcher suggests that the company should increase social media marketing activities and select suitable content creators to continuously enhance purchasing decisions among consumers for Skintific products.